Skeleton for dinner - Cuyler, Margery (Chicago, Illinois : Albert Whitman & Company, 2013)
Big Witch and Little Witch have made stew and want to invite their friends to eat with them, but Skeleton mistakes the guest list for a menu and takes off to warn Ghost and Ghoul, who hide with him in the haunted forest.
Keywords: Miscommunication -- Fiction; Fear -- Fiction; Skeleton -- Fiction; Witches -- Fiction; JUVENILE FICTION / Holidays & Celebrations / Halloween; JUVENILE FICTION / Horror & Ghost Stories; JUVENILE FICTION / Humorous Stories; Humorous fiction